A comparison of methods for teaching receptive labeling to children with autism spectrum disorders: A systematic replication. Issue 3 (6th June 2014) - Grow, Laura L.; Kodak, Tiffany; Carr, James E.
Abstract : Previous research has demonstrated that the conditional‐only method (starting with a multiple‐stimulus array) is more efficient than the simple‐conditional method (progressive incorporation of more stimuli into the array) for teaching receptive labeling to children with autism spectrum disorders (Grow, Carr, Kodak, Jostad, & Kisamore, 2011). The current study systematically replicated the earlier study by comparing the 2 approaches using progressive prompting with 2 boys with autism. The results showed that the conditional‐only method was a more efficient and reliable teaching procedure than the simple‐conditional method. The results further call into question the practice of teaching simple discriminations to facilitate acquisition of conditional discriminations.